When Hope, Gratitude, and Mindfulness Meet: A Positive Psychology Approach to Job Performance - Rahmawati, Atsna Sabatini; Pertiwi, Talitha Lintang (Journal of Educational, Health and Community Psychology, 2025)
Job performance is a highly relevant topic in industrial and organizational psychology; however, its association with internal psychological strengths such as hope, gratitude, and mindfulness has been relatively underexplored, particularly across different cultural contexts. Existing studies on job performance tend to emphasize negative factors, such as stress and workload, while the role of positive psychological factors remains comparatively neglected, especially in Indonesia. The present study examined the contribution of hope, gratitude, and mindfulness to job performance among 205 employees in Indonesia using a cross-sectional quantitative design. Data were collected via an online questionnaire and analyzed using multiple linear regression. The results indicated that the research model was significant, F (3, 201) = 61.00, p < .001, R² = .477, showing that the three variables jointly explained approximately 48% of the variance in job performance. Specifically, hope and mindfulness had positive and significant effects on job performance, whereas gratitude did not demonstrate a significant positive effect. These findings underscore the importance of considering individual strengths—namely hope, gratitude, and mindfulness—in recruitment processes as well as in the design of organizational training and intervention programs aimed at enhancing employee performance.